Difficulties experienced by nursing assistants in urgency and emergency units: An integrative review (Research, Society and Development, 2021)
Urgency and emergency care has been the subject of discussion in several countries, due to its impact on health care and on morbidity and mortality indicators. In Brazil, several authors have been discussing the attention paid to urgencies and emergencies under different approaches. The objective of this study is to investigate the scientific evidence about the main difficulties experienced by nurses in care in urgent and emergency units in the period from 2015 to 2020. This is a descriptive research with a qualitative approach added through the Review method Integrativa da Literature (RIL), in the LILACS, BDENF AND MEDLINE. For data analysis, Bardin's proposal was used, with the aid of the IRAMUTEC program in the exploration of the material. 3 classes were obtained, namely: The importance of nurses in the hospital environment of urgency and emergency; Exposure of nursing professionals to physical and psychological stress factors that affect the quality of patient care; The development of assistance related to material resources and infrastructure in urgent and emergency services. It was possible to observe the inappropriate working conditions that nursing professionals are exposed to in their daily lives, which put them at risk for the acquisition of infectious diseases, exposure to violence, occupational stress.